Making sense of Cbp/p300 loss of function mutations in skin tumorigenesis. Issue 1 (9th October 2019) - Anastasi, Sergio; Alemà, Stefano; Segatto, Oreste
Abstract: CBP and p300 are highly homologous lysine acetyltransferases involved in cell cycle regulation, DNA synthesis and DNA repair. Loss of function mutations of CBP and p300 are found in about one‐third of cutaneous squamous cell carcinoma (cSCC) and often co‐occur, yet their role in cSCC pathogenesis is unclear. Writing in The Journal of Pathology, Ichise and colleagues modeled combined heterozygous loss of Cbp/p300 in mouse keratinocytes expressing a transgenic Hras S35 allele that allows selective coupling of Hras to the Erk pathway. Epidermal thickening caused by expression of Hras S35 was exacerbated by reduced dosage of Cbp/p300 and eventually resulted in development of skin papillomas. This phenotype was associated with reduced expression of Mig6, an Egfr feedback inhibitor, and attendant enhancement of Egfr signaling to the Ras‐Erk pathway. This model provides a mechanistic framework for understanding how Cbp/p300 loss of function mutations impact on skin tumorigenesis and suggests potential therapeutic options in CBP/p300 mutated human cSCC. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.